2019
DOI: 10.3897/zookeys.862.35727
|View full text |Cite
|
Sign up to set email alerts
|

Size variation and geographical distribution of the luminous earthworm Pontodrilus litoralis (Grube, 1855) (Clitellata, Megascolecidae) in Southeast Asia and Japan

Abstract: The luminous earthworm Pontodriluslitoralis (Grube, 1855) occurs in a very wide range of subtropical and tropical coastal areas. Morphometrics on size variation (number of segments, body length and diameter) and genetic analysis using the mitochondrial cytochrome c oxidase subunit 1 (COI) gene sequence were conducted on 14 populations of P.litoralis from Southeast Asia and Japan. Statistical inference on morphometric data revealed significantly different size variations in the body length and diameter among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…A British television program 26 presented by David Attenborough showed that the French luminous earthworm Avelona ligra glowed when attacked by the carabid beetle, but the beetle consumed the luminescent worm without any hesitation. We suggest that the absence of bioluminescence in P. longissimus may be associated with its presence in habitats with low predation pressure, whereas P. litoralis acquired a bioluminescent property during evolution that enabled it live on the surface of the beach, which is rich in nutrition and food sources 3 , 27 as well as potential predators.
Figure 4 ( A ) The microhabitat of Pontodrilus litoralis from Aichi Prefecture, Japan.
…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A British television program 26 presented by David Attenborough showed that the French luminous earthworm Avelona ligra glowed when attacked by the carabid beetle, but the beetle consumed the luminescent worm without any hesitation. We suggest that the absence of bioluminescence in P. longissimus may be associated with its presence in habitats with low predation pressure, whereas P. litoralis acquired a bioluminescent property during evolution that enabled it live on the surface of the beach, which is rich in nutrition and food sources 3 , 27 as well as potential predators.
Figure 4 ( A ) The microhabitat of Pontodrilus litoralis from Aichi Prefecture, Japan.
…”
Section: Discussionmentioning
confidence: 97%
“…The earthworm genus Pontodrilus Perrier, 1874, displays various unique characteristics. The littoral earthworm P. litoralis (Grube, 1855) is distributed on the tropical and subtropical coasts of the Atlantic, Indian and Pacific Oceans 1 3 and is known to be bioluminescent 4 – 7 . The luminescent system of P. litoralis has been shown to be a luciferin-luciferase type reaction triggered by hydrogen peroxide, with a fluorescence compound acting as a light emitter 7 , although the chemical structure of the luciferin remains uncertain and the luciferase gene has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…A British television program [26] presented by David Attenborough showed that the French luminous earthworm Avelona ligra glowed when attacked by the carabid beetle, but the beetle consumed the luminescent worm without any hesitation. We consider that the absence of bioluminescence in P. longissimus may correlate with the habitats with low-predation pressure, whereas P. litoralis acquired a bioluminescence property during evolution that enables it to enter the surface environment of the beach, which is rich in nutrition and food sources [3,27] as well as in potential predators.…”
Section: Discussionmentioning
confidence: 99%
“…The littoral earthworm P. litoralis was collected at a sandy region of one of the following beaches [3,8]: Wonnapa beach, Amphoe Mueang Chon Buri, Chonburi, Thailand (13°15'55.6"N 100°55'29.3"E), Kowa beach, Chita, Aichi prefecture, Japan (34°46'23.3"N 136°54'52.7"E) and Kira Waikiki Beach, Nishio, Aichi prefecture, Japan (34°46'55.2"N 137°05'48.3"E). P. longissimus was collected from Tambon Muang Klang, Amphoe Kaper, Ranong, Thailand (9°37'26.7"N 98°28'08.6"E).…”
Section: Specimens and Species Identi Cationmentioning
confidence: 99%
See 1 more Smart Citation